Denture disinfection by microwave irradiation: A randomized clinical study - Ribeiro, Daniela Garcia; Pavarina, Ana Claudia [UNESP]; Dovigo, Lívia Nordi [UNESP]; Palomari Spolidorio, Denise Madalena [UNESP]; Giampaolo, Eunice Teresinha; Vergani, Carlos Eduardo [UNESP] (Elsevier B.V., 2009)
Objective: This study evaluated the clinical effectiveness of two exposure times of microwave irradiation on the disinfection of complete dentures.Methods: Biofilm samples were collected from dentures of 30 patients, who were randomly divided into two experimental groups of 15 subjects each: Group 1-patients had their maxillary denture microwaved for 3 min (650 W); Group 2-patients had their maxillary denture microwaved for 2 min (650 W). Denture biofilm samples were taken with swabs, before left side surfaces) and after (right side surfaces) microwave irradiation. All microbial material was plated on selective media for Candida spp., Staphylococcus spp., mutans streptococci and a non-selective media. After incubation (48 h/37 degrees C), the number of colony-forming units (cfu/mL was counted. microorganisms which grew on selective media were identified using biochemical methods. The data were statistically analyzed by Kruskal-Wallis test, followed by Dunn's post-test (alpha = 0.05).Results: Microwave irradiation for 3 min (Group 1) resulted in sterilization of all dentures evaluated. After microwave irradiation for 2 min (Group 2), a significant decrease in Candida spp. (P = 0.0062), Staphylococcus spp. (P = 0.0178), mutans streptococci (P = 0.0047) and non-identified species (P < 0.0001) was achieved in comparison with the cfu/mL obtained before irradiation. The colonies grown after 2 min of microwave irradiation were identified as Candida albicans, non-aureus Staphylococci and Streptococcus mutans.Conclusion: Microwave irradiation for 3 min may be a potential treatment to prevent cross-contamination. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Microwaves; Complete denture; Sterilization; Disinfection; Infection control